Distribution of serotypes and genotypes of Salmonella enterica species in French pig production. (19th October 2013) - Denis, M.; Houard, E.; Fablet, A.; Rouxel, S.; Salvat, G.
Abstract : The population of Salmonella found at various stages of pig production in France was characterised to analyse the distribution and spread of Salmonella in the pig production chain. We serotyped and genotyped by PFGE 174 isolates collected from breeding pigs from breeding farms, 163 collected from breeding pigs from production farms, and 325 collected from fattening pigs. Forty‐seven serovars and 110 genotypes were identified. The major serovars were S Derby (263 isolates) and S Typhimurium (162 isolates). The percentage of S Derby isolates decreased slightly through the production system (44.3, 41.1 per cent and 36.5 per cent) and 79.1 per cent of the S Derby isolates were distributed in the five genotypes common to all three stages. The percentage of S Typhimurium isolates was high for slaughter pigs (40.8 per cent) and 43 of the 46 S Typhimurium genotypes were only identified at this stage. Distributions of S Derby and S Typhimurium between breeding and fattening pigs were different. S Derby was found throughout the pig production pyramid, suggesting that this serotype may be transmitted by the transfer of animals between herds. The presence of multiple S Typhimurium genotypes in fattening pigs suggests that there were many sources of contamination at this stage, with fattening pigs having higher levels of exposure and/or sensitivity to this serotype.